‘ANNE GOES ROGUE FOR ABORTION RIGHTS!’ EXPLORING DISCURSIVE MATERIALIZATION ACROSS AND BEYOND ONLINE PLATFORMS - Myles, David (AoIR Selected Papers of Internet Research, 2018)
This presentation examines the social media campaign #SupportIslandWomen that was undertaken by reproductive rights activists in Prince Edward Island (PEI). The initiative gained popularity in 2016 due to both the off- and online circulation of posters throughout PEI landmarks depicting the Green Gables-like image of a young girl (“rogue Anne”) wearing red braids and a bandana. These posters showcased specific hashtags that encouraged debates on various online platforms. For this study, we underline how human actors invoked the symbolic ‘figure’ of rogue Anne to give weight to their own arguments by speaking or acting in her name. By ‘figure’, we mean any symbolic entity that is materialized through interaction and that possesses agency, or the ability to make a significant difference in interaction. Hence, our study examines the processes through which rogue Anne was made present in interaction, the role of digital (online) and physical (offline) affordances in the materialization of this figure, and the differentiated effects that these invocations generated. To do so, we build our dataset by performing non-participant observation on social media platforms and by exploring Canadian blogs and newspapers. Drawing from organizational discourse theory, our results show that invoking the figure of rogue Anne allowed for pro-choice collectives to assert their authority in abortion debates by labelling the fictional character as a modern feminist icon. They also underline the importance of studying the intervention of symbolic figures, their effects, and their materialization within political initiatives that incorporate and go beyond the practice of ‘hashtagging’.